The training of international level distance runners - Tjelta, L. I. (International Journal of Sports Science & Coaching, 2016)
A limited number of studies have examined the distribution of training at different intensities during longer training periods among elite runners. Runners who want to reach international level in distance running should run =110km/week at the age of 18-19 years. For senior runners, it appears that training volumes around 150-200km/week are appropriate for 5000 and 10,000m runners and 120-160km/week for 1500m runners. It also appears to be beneficial to combine these weekly training volumes with two to four sessions per week at the velocity at the anaerobic threshold pace, and one to two sessions per week above velocity at the anaerobic threshold pace during the preparation period. For runners who compete over distances from 1500 to 10,000m, it seems appropriate to reduce the number of sessions carried out at velocity at the anaerobic threshold pace and to increase the number of sessions at specific race pace in the pre-competition period and during the competition period. Top results for the marathon can be achieved by a "low volume/high intensity model" (150-200km/week), as well as by a "high volume/low intensity model" (180-260km/week).